Measurement of the Attitude of the Members of SHGs Toward Self-Help Groups in Haryana - Yadav, Jyoti; Kaur, Ravinder; Mishra, Suyash (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : The current study focused on measuring the attitudes of the members of SHGs toward the groups. The emergence of the Self-Help Groups-Bank Linkage Program (SHG-BLP) as a prominent microfinance approach and its subsequent substantial expansion for empowering women induced the attitude of the members toward the SHGs. Methodology : The principal component analysis (PCA) was employed to analyze the data through SPSS. Data were collected from 400 SHG rural women members through personal interviews with the help of a structured questionnaire using a 20-item attitude scale. Findings : The factor analysis revealed five predecessors of attitude: â€œCoping up ability,â€ â€œBenefits of SHGs,â€ â€œEntrepreneurship development,â€ â€œEconomic benefits,â€ and â€œPersonality development.â€ The beneficiaries were satisfied with the work of SHGs to develop their coping ability to face adverse situations confidently, but they were least satisfied with the outcomes of SHGs in terms of personality development. Practical Implications : Based on the findings, the study recommended that SHGs should work toward promoting entrepreneurial activities and focus on improving their functioning. SHGs should provide training and counseling services to develop the administrative and leadership skills of members, which significantly contribute to developing rural womenâ€™s positive attitudes toward SHGs. Originality : Unlike the previous studies, this study provided a robust and pertinent instrument to measure beneficiariesâ€™ attitudes toward SHGs and deliver a crucial tool for program assessment and improvement based on attitudinal aspects of rural impoverished people connected to SHGs, especially in Haryana.